PROBLEMS OF HIGHER SCHOOL IN THE ASPECT BOLOGNA PROCESS - L.V. Kondrashova (Academy of Cognitive and Natural Sciences, 2004)
The advantages and disadvantages o f higher education modernization in accordance with Boulogne agreement are considered in the article; the problem o f higher pedagogical school o f Ukraine are concretized.